Scalar current limit from the beta-neutrino correlation: the WISArD experiment. (August 2019) - Araujo-Escalona, V.; Alfaurt, P.; Ascher, P.; Atanasov, D.; Blank, B.; Daudin, L.; Fléchard, X.; Gerbaux, M.; Giovinazzo, J.; Grévy, S.; Kurtukian Nieto, T.; Liénard, E.; et al.
Abstract: Beta - neutrino correlation measurements are key in the research of physics beyond the Standard Model. In pure Fermi beta transitions, the beta-neutrino correlation coefficient, a βν, is sensitive to the presence of scalar currents. The present limits were established by experimental studies of various nuclear systems with allowed Fermi transitions. A new experiment to improve the constraints on scalar currents is being developed, by the WISArD collaboration at ISOLDE/CERN, where the aim is to measure the energy shift of the β-delayed protons emitted from the isobaric analogue state of the 32 Ar ground state. To enhance the sensitivity, protons and positrons are guided by a strong magnetic field and measured in coincidence between the two detection configurations located on both sides of a catcher foil in which the radioactive samples are implanted. Kinematic energy shifts of the protons in coincidence with positrons, in the same or opposite hemisphere of the catcher foil, will be more or less pronounced as a function of the possible scalar current component of the weak interaction. Details of the apparatus and preliminary results of the experiment are presented.